Analysis of Wattpad E-Community: A Model-Based Virtual Collaboration - Celerino Arthur N. Malle; Maria Cristal N. Velez (Universitas PGRI Semarang, 2023)
This study conducted an Analysis of Wattpad E-Community: A Model-Based Virtual Collaboration. Specifically, it sought to answer the following: (1) What information can be obtained based on the analysis of Wattpad E-Community in terms of (a) strengths, (b) weakness, (c) opportunities, and (d) threats?; and (2) What program can be proposed based on the S.W.O.T analysis of Wattpad E-Community?. This descriptive-quantitative research collected data via survei which were analyzed and interpreted using Weighted Mean, ranking, and verbal descriptors. The SWOT analysis indicated that ideal platform, learning experience, and sociable environment are among the group’s strengths, whereas excessive liberty, technical difficulties, and exclusivity belong to its weaknesses. In addition, the discovered opportunities in the group include possibility to meet and learn from professionals/expert, development of online learning community, and potential feasibility in data gathering, while possibility to transfer to another e-community, cyber security hazards, and frequent power outages are considered as threats. Therefore, it is recommended to propose the implementation of Project VIBE (Virtual, Interactive, and Boundless Engagement), alongside the application of the improvements and revisions generated from the results of the SWOT Analysis.